2001
DOI: 10.1128/aem.67.12.5621-5625.2001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Homolactic Fermentation by Kluyveromyces lactis Strains Defective in Pyruvate Utilization and Transformed with the Heterologous LDH Gene

Abstract: A high yield of lactic acid per gram of glucose consumed and the absence of additional metabolites in the fermentation broth are two important goals of lactic acid production by microrganisms. Both purposes have been previously approached by using a Kluyveromyces lactis yeast strain lacking the single pyruvate decarboxylase gene (KlPDC1) and transformed with the heterologous lactate dehydrogenase gene (LDH). The LDH gene was placed under the control the KlPDC1 promoter, which has allowed very high levels of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 18 publications
0
50
0
1
Order By: Relevance
“…Bianchi et al used K. lactis strains lacking either PDC activity or PDC and PDH activities, transformed with the LDH gene placed under the control of the promoter of KlPDC1 gene and cloned into stable multicopy vector. Transgenic K. lactis strains showed remarkable improvement under the fed-batch condition (3).…”
mentioning
confidence: 99%
“…Bianchi et al used K. lactis strains lacking either PDC activity or PDC and PDH activities, transformed with the LDH gene placed under the control of the promoter of KlPDC1 gene and cloned into stable multicopy vector. Transgenic K. lactis strains showed remarkable improvement under the fed-batch condition (3).…”
mentioning
confidence: 99%
“…16) Additional inactivation of PDH activity was required to increase the yield of L-lactic acid in K. lactis, 9) although this was accompanied by a significant growth defect, which is not considered desirable, particularly in fermentation processes. In C. utilis, however, inactivation of PDC activity alone was sufficient to obtain high yields of L-lactic acid, the yield being 95.1% (103.3 g/l; >99:9% e.e.)…”
Section: Discussionmentioning
confidence: 99%
“…This relatively high optimal temperature is also advantageous because lactic acid at high concentrations easily becomes solidified in the medium due to low solubility. Usually, fermentation of S. cerevisiae and K. lactis is limited at lower temperatures from 30 to 32 C. [5][6][7][9][10][11][12][13][14] The pH value of the medium also appeared to be important for the production of L-lactic acid, since a previous study showed that adjustment of pH was effective for the high expression of PDC in C. utilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is more critical as we attempt to replace petroleum-based plastics with renewable PLA-based plastics, which would require production of the base chemical in large quantities and lignocellulosic biomass as the feedstock for fermentation. Biocatalysts currently being developed to reduce the cost of production of optically pure isomers of lactic acid include Kluyveromyces (Bianchi et al, 2001;Porro et al, 1999), Saccharomyces (van Maris et al, 2004;Saitoh et al, 2005), Pichia (Ilmen et al, 2007), Rhizopus (Skory, 2000) and Lactobacillus (Liu et al, 2007); however, Escherichia coli stands out as an excellent microbial biocatalyst for this purpose (Dien et al, 2001;Grabar et al, 2006). E. coli is a well studied bacterium that uses glycolysis via the Embden-Meyerhoff-Parnas (EMP) pathway to convert hexose sugars into a mixture of acids (lactic, acetic, formic and succinic) and ethanol (Clark, 1989).…”
Section: Lactococcus Lactis and Lactococcus Casei As Well Asmentioning
confidence: 99%